DYNAMIC ANALYSIS OF INDUSTRIAL PRODUCTION IN KASHKADARYA REGION IN THE CONTEXT OF REGIONAL ECONOMIC DEVELOPMENT - Valiyev, Oybek Shukhrat-ugli (THE INNOVATION ECONOMY, 2026)
This study analyzes industrial production growth across districts of the Kashkadarya region of Uzbekistan during 2010–2025. Using district-level data on year-on-year industrial growth, the paper examines spatial differences, growth instability, and regional responses to economic shocks. A fixed effects panel model is applied to account for stable district characteristics and common time effects, including the COVID-19 period. The results show clear spatial differences in industrial growth, with stable performance in urban and industrial centers and more unstable growth in peripheral districts. The COVID-19 shock increased existing regional inequalities, and recovery after the crisis was uneven across districts. Overall, the findings show no full convergence in industrial growth but suggest club convergence among core districts. The study highlights the need for region-specific industrial policies to support stable and balanced regional development.